2009
DOI: 10.1016/j.atmosenv.2008.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine disrupting chemicals in indoor and outdoor air

Abstract: The past 50 years have seen rapid development of new building materials, furnishings, and consumer products and a corresponding explosion in new chemicals in the built environment. While exposure levels are largely undocumented, they are likely to have increased as a wider variety of chemicals came into use, people began spending more time indoors, and air exchange rates decreased to improve energy efficiency. As a result of weak regulatory requirements for chemical safety testing, only limited toxicity data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
304
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 463 publications
(321 citation statements)
references
References 134 publications
(197 reference statements)
13
304
1
3
Order By: Relevance
“…24,36 Kinetic formation curves for (SCN) 2 •− at 480 nm with different PPB concentrations gave a bimolecular rate constant (k T ) of 7.70 ± 0.39 × 10 9 M −1 s −1 using eq 2 ( Figure S1). 22 and a double peak was obviously found around 420 nm ( Figure S2), which was assigned to phenoxyl radical formed by radical cation in aqueous solution.…”
Section: Homentioning
confidence: 99%
See 1 more Smart Citation
“…24,36 Kinetic formation curves for (SCN) 2 •− at 480 nm with different PPB concentrations gave a bimolecular rate constant (k T ) of 7.70 ± 0.39 × 10 9 M −1 s −1 using eq 2 ( Figure S1). 22 and a double peak was obviously found around 420 nm ( Figure S2), which was assigned to phenoxyl radical formed by radical cation in aqueous solution.…”
Section: Homentioning
confidence: 99%
“…Parabens are important antimicrobial preservatives that are widely used in many commercial products such as cosmetics, shampoo, creams, and paper. 1,2 The persistence and increasing amount of these emerging contaminants (ECs) in surface water and sewage systems have been reported in many countries. 3−5 This has raised concern about their potential risks to aqueous organisms and humans due to their acute and chronic toxicity, 6,7 as well as estrogenic effect of propylparaben (PPB).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Moreover, many chemicals identified as endocrine-disrupting compounds (mainly phthalates, o-phenylphenol, 4-nonylphenol and adhesive 4-tert-butylphenol with typical concentrations in the range of 50-1500 ng m −3 ) were detected in indoor air and dust [112,113]. Evidence from several studies has revealed that air pollution is associated with the increased morbidity and mortality of breast cancer patients [114][115][116][117].…”
Section: Atmospheric Pollutantsmentioning
confidence: 99%
“…These substances are common additives to household insect repellents, food packaging materials, food storage containers, children's toys, electronics and electric equipment, building and construction materials, paints, furniture, carpets, mattresses, textiles, and personal care products, as shown in Table 1 (4,5). Numerous studies have observed that chemicals contained within household items are released over time into the home environment, and are subsequently detectable in household dust, food and indoor air samples, thus constituting multiple possible pathways of exposure of young children to these chemicals, as described below (4,6,7).…”
Section: Introductionmentioning
confidence: 99%